The Triglyceride‐Glucose (TyG) Index and Incident Diabetes and Cardiovascular Events in People Living With HIV‐1 Infection. A 14‐Year Observational Cohort Study - Daniele Pastori; Gianluca Gazzaniga; Tommaso Brogi; Marco Rivano Capparuccia; Caterina Fimiani; Claudio Mastroianni; Ivano Mezzaroma (European Journal of Clinical Investigation, 2026)
ABSTRACT Background People living with HIV (PWH) are at increased risk for metabolic and cardiovascular diseases. However, there is no structured prevention strategy for these subjects. The triglyceride‐glucose (TyG) index has shown predictive value for Type 2 diabetes mellitus (T2DM) and cardiovascular events (CVEs) in the general population, but its utility in PWH remains unclear. Methods We conducted a retrospective study including 477 PWH without baseline T2DM. TyG index was calculated as follows: ln[fasting triglycerides (mg/dL) × fasting glucose (mg/dL)]/2. ROC analysis was used to identify the optimal TyG threshold for T2DM, and logistic regression analysis was used to evaluate the association with T2DM. The association between TyG index and CVEs was investigated using Kaplan–Meier survival analysis and Cox proportional hazards regression models. Results 477 PWH were included. Median age was 38 years and 26% were women. During a median follow‐up of 14.2 years, 38 participants developed T2DM and 45 experienced CVEs. The TyG index demonstrated fair discrimination for incident T2DM (AUC: 0.675, 95% CI 0.591–0.759), with an optimal threshold of 4.78. Participants with TyG ≥ 4.78 had a higher risk of developing T2DM (aOR 2.86, 95% CI 1.35–6.12). PWH in the highest TyG tertile had also higher risk for CVEs compared with those in the lowest tertile (aHR 3.31, 95% CI 1.10–9.97). Conclusion In PWH, a higher TyG index was independently associated with an increased risk of both T2DM and CVEs over long‐term follow‐up. The TyG index represents a practical, low‐cost tool for early metabolic risk stratification in this population.